Current Status, Challenges and Strategies of Artificial Intelligence and E-learning the UAE Military Education System - Ali Alnaqbi, Ali Mohamed; Md Yassin, Azlina (International Journal of Sustainable Construction Engineering and Technology, 2021)
Recently, UAE has adopted Artificial Intelligence (AI) and e-learning system in several fields including education. Together with the institutions running on conventional educational system, military colleges have also embrassed this new technology. This study assessed the current status of adoption, challenges and strategies of using AI based e-learning system in the UAE military based colleges. The study was carried out based on the perception of the teachers and students of Joint Command and Staff College (JCSC). A set of the questions was presented to the 50 teachers and 157 students for highlighting the level of agreement for each question. The questions were devided into three sections as level of adoption, challenges, and strategies in using AI based e-learning education system. The study found that for current status, AI and e-learning have got siginificant popularity in the education system due to high level of flexibility. While the challenges, the lack of human relations between teacher and student is reported as the major challenge faced in adoption of AI based e-learning system. Finally, for the strategies, the respondents indicated that the UAE is trying to develop plans and alternatives to address the discrepancy between traditional teaching and artificial intelligence methods adapted in the military college. This study provides a valuable source of information for devicing strategies to promote the uses of these modern tools and also motivate the students to get the maximum benefits of AI and e-learning technologies.